A simple and easy non‐derivatization gas chromatography‐mass spectrometry method for simultaneous quantification of valproic acid, gabapentin, pregabalin, and vigabatrin in human plasma - Jin, Peng; You, Yu‐xin; Zhao, Lin‐lin; Zhao, Yan‐lin; Zheng, Xiao‐xiao; Du, Yan; Tang, Dao‐quan (Journal of separation science, 2023)
Immunoassays are currently not available in commercial kits for the quantification of valproic acid, vigabatrin, pregabalin, and gabapentin, which also cannot suffer the limitations of interferences of substances with similar structures. Chromatography is a good alternative to immunoassay. In this study, a simple and robust non‐derivatization gas chromatography‐mass spectrometry method for simultaneous determination of the above four drugs in human plasma was developed and validated for therapeutic drug monitoring purposes. This method employed benzoic acid as the internal standard with hydrochloric acid for plasma acidification and ACN for precipitate protein. The supernatant was directly injected into gas chromatography‐mass spectrometry for analysis. Good linearity was obtained with linear correlation coefficients of the four analytes of 0.9988–0.9996. Extraction recoveries of valproic acid, vigabatrin, pregabalin, and gabapentin were respectively in the ranges of 91.3%–94.5%, 90.0%–90.9%, 90.0%–92.1%, and 88.0%–92.2% with the relative standard deviation values less than 12.6%. Intra‐ and inter‐batch precision and accuracy, and stability assays were all acceptable. Taken together, the novel method developed in this study provided easy plasma pretreatment, good extraction yield, and high chromatographic resolution, which has been successfully validated through the quantification of valproic acid in the plasma of 46 patients with epilepsy.